2022
DOI: 10.1111/1440-1703.12320
|View full text |Cite
|
Sign up to set email alerts
|

Review: Genetic structure and local adaptation in natural forests of Cryptomeria japonica

Abstract: Cryptomeria japonica is a very important and useful forestry tree in Japan and there are vast areas of plantation area that occupy 44% of the total man-made forest in the country. Natural populations have declined as a result of logging and overexploitation for more than a thousand years. The natural distribution of C. japonica is from Aomori Prefecture to Kagoshima Prefecture and it has adapted to widely different environments in Japan. In China, the variety C. japonica var. sinensis is distributed. The genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Some C. japonica ne roots can form arbuscular mycorrhizas (AM) primarily in the 1st root order (Hishi et As Yaku cedar has distinctly low aboveground productivity during the early growth stage in its native habitat (Takashima et al 2009;Itaka et al 2013) and in the common garden (Ohta et al 2019;Azuma et al 2023), ne root morphological traits of Yaku cedar were also differentiated from trees of other provenances, despite large differences in soil chemical properties between the present common garden and its unique native habitat on Yakushima Island where higher soil phosphorus contents are observed owing to volcanic ash (Mukai et al 2016). Furthermore, Yaku cedar has a relatively long genetic distance from Yanase and Yoshino cedars (Tsumura 2023), implying the limits of functional plasticity against growing environments and the consistency of inherent characteristics determined by the genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…Some C. japonica ne roots can form arbuscular mycorrhizas (AM) primarily in the 1st root order (Hishi et As Yaku cedar has distinctly low aboveground productivity during the early growth stage in its native habitat (Takashima et al 2009;Itaka et al 2013) and in the common garden (Ohta et al 2019;Azuma et al 2023), ne root morphological traits of Yaku cedar were also differentiated from trees of other provenances, despite large differences in soil chemical properties between the present common garden and its unique native habitat on Yakushima Island where higher soil phosphorus contents are observed owing to volcanic ash (Mukai et al 2016). Furthermore, Yaku cedar has a relatively long genetic distance from Yanase and Yoshino cedars (Tsumura 2023), implying the limits of functional plasticity against growing environments and the consistency of inherent characteristics determined by the genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the Japanese cedar is now only locally distributed in restricted natural forests, but since at least 7000 years ago until modern times, it has been widely distributed in the Japanese archipelago except in Hokkaido, and was the dominant species in the temperate zone of Japan due to its large biomass. Tsumura (Tsumura, 2023) outlines the distributional transitions and local adaptations inferred from the genetic variation of the Japanese cedar in the Japanese archipelago and China, and proposes methods to prevent genetic disturbance of geographically differentiated populations. Genetic differentiation occurred as a result of restricted gene flow and local adaptation due to distributional area fragmentation or fluctuation with warming from the coldest glacial period and recolonization from the Hypsithermal period to the modern era.…”
Section: Figurementioning
confidence: 99%
“…Its amount of academic information is comparable to that of the European beech ( Fagus sylvatica ), the Scots pine ( Pinus sylvestris ), and the Norway spruce ( Picea abies ) in Europe (e.g., Benavides et al, 2021; Schulze, 2000; Vila‐Cabrera et al, 2015). In the case of the Japanese cedar, the genetic diversity remained after the presence of several refugia even in the Last Glacial Maximum (LGM; Takahara et al, 2023; Tsumura, 2022), and therefore, it is expected that the geographic, genetic, and functional variations are also large. Based on these characteristics, the Japanese cedar will provide a good material for investigating the response of each local forest ecosystem under climate change, based on the geographic functional differentiation and its cascading effects.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Our editorial team will continue to publish original papers covering a diverse range of topics in ecology. Last year, we published original papers on population ecology (e.g., Tsumura, 2023;Worth et al, 2023), community ecology (e.g., Chang et al, 2023;Ohkawara & Taijiri, 2023), ecosystem ecology (e.g., Matsumoto et al, 2023), conservation ecology (Hirano et al, 2023;Tsujimoto et al, 2023), plant-animal interactions (e.g., Kawata & Takimoto, 2023;S anchez-Collazo et al, 2023), behavioral ecology (Bibi et al, 2023), and physiological ecology (e.g., Rooney et al, 2023;Sugimoto & Ishida, 2023), among others. Our papers also cover topics that are of high societal interest, including the analysis of the ongoing invasion of the whitefooted ant (Technomyrmex brunneus Forel) in eastern Asia (Putri & Cronin, 2023), recent expansion of a Japanese land leech (Haemadipsa japonica Whitman) associated with the migration of sika deer (Morishima et al, 2023) and future persistence of high-mountain lizards worldwide under climate change (Moreira et al, 2023).…”
mentioning
confidence: 99%